KOMPETENSI ADMINISTRASI SEKOLAH DI SMA NEGERI 5 LUWU TIMUR - Sitti Rahma Mutmainna; Wahira Wahira (UNM (Universitas Negeri Makasar), 2022)
The purpose of this study is to explore competence that has the existing school administration administration of the SMA Negeri 5 Luwu Timur administration and the supporting factors and competence increases the existing school administration administration of SMA Negeri 5 Luwu Timur. This research approach is qualitative with a descriptive type of research. The study is conducted at the SMA Negeri 5 Luwu Timur. The source of the data in this study is the principal, the school administration and the teacher. Data collection techniques of observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and deduction drawing. Data verification checking using the triulation technique. Research indicates that the school administration at SMA Negeri 5 Luwu Timur already has personality competence, social competence, managerial competence but still lack technical competence. In turn, contributing factors include experience and motivation in work. The inhibitors are the lack of the tools and training for school administration.